Radiation therapy in treatment of Rosai–Dorfman disease: literature review and report of a patient with cutaneous form - Vsevolod G. Potapenko (IP Habib O.N., 2021)
RosaiDorfman disease (RDD) is a rare variant of the nonlangergans histiocytosis. Various presentation, systemic and localised forms and limited publications make diagnostics and prompt management difficult.